2020
DOI: 10.1016/j.compositesa.2020.105862
|View full text |Cite
|
Sign up to set email alerts
|

An experimental and numerical investigation into damage mechanisms in tapered laminates under tensile loading

Abstract: An experimental and numerical investigation into damage mechanisms in tapered laminatesunder tensile loading

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 52 publications
0
20
0
Order By: Relevance
“…S 33 (MPa) [19] S 13 (MPa) [19] n f [23] n g (MPa when the initiation condition presented in Equation ( 4) is first met (point A in Fig. 11) -and show the clear difference in distributions between the different ply termination methods.…”
Section: Properties Of Cohesive Interface Elementsmentioning
confidence: 98%
See 2 more Smart Citations
“…S 33 (MPa) [19] S 13 (MPa) [19] n f [23] n g (MPa when the initiation condition presented in Equation ( 4) is first met (point A in Fig. 11) -and show the clear difference in distributions between the different ply termination methods.…”
Section: Properties Of Cohesive Interface Elementsmentioning
confidence: 98%
“…To gain ply-level stress distributions and a more fundamental understanding of how the scarfed ply drops change the stress distributions around the ply drop regions, numerical analyses were conducted based on a method previously demonstrated to accurately capture delamination type failures by multiple authors [18][19][20], which makes use of a custom written mesh generation code using the MATLAB software package.…”
Section: Numerical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, Zhang et al. (2020) developed high-fidelity models capable of accurately predicting both the failure mode and strength of modesty and severely tapered composite subjected to tensile loading.…”
Section: Introductionmentioning
confidence: 99%
“…Although, in some studies of tapered geometries delamination cracks were reported to be the only damage mode [1], a matrix crack is usually formed in the resin pocket prior to delamination cracks propagating from the pocket into the laminate. Development of delamination cracks, being one of the critical damage modes, has attracted more attention both experimentally and numerically (see [2] and references therein), while the initial matrix cracks are usually disregarded.…”
Section: Introductionmentioning
confidence: 99%